2017
DOI: 10.3390/nu9030277
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Hepcidin Levels during an Intensified Training Period in Well-Trained Female Long-Distance Runners

Abstract: Iron is essential for providing oxygen to working muscles during exercise, and iron deficiency leads to decreased exercise capacity during endurance events. However, the mechanism of iron deficiency among endurance athletes remains unclear. In this study, we compared iron status between two periods involving different training regimens. Sixteen female long-distance runners participated. Over a seven-month period, fasting blood samples were collected during their regular training period (LOW; middle of February… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Our data show that resting serum hepcidin concentrations (12-15 h after the last training session) were elevated at the beginning of the high load training phase with a rapid return to baseline within only a few days, when rowers adapted to the high workloads (Figure 2A). Our findings are consistent with results from Ishibashi et al (2017) who observed elevated hepcidin expression levels during an intensified training period in long-distance, female runners. Ma et al (2013) compared resting serum hepcidin levels in highly trained female distance runners mid-season to a low exercise control group and showed that there was no difference between runners and controls for serum hepcidin levels midseason, suggesting that hepcidin was not chronically elevated with sustained high training loads.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data show that resting serum hepcidin concentrations (12-15 h after the last training session) were elevated at the beginning of the high load training phase with a rapid return to baseline within only a few days, when rowers adapted to the high workloads (Figure 2A). Our findings are consistent with results from Ishibashi et al (2017) who observed elevated hepcidin expression levels during an intensified training period in long-distance, female runners. Ma et al (2013) compared resting serum hepcidin levels in highly trained female distance runners mid-season to a low exercise control group and showed that there was no difference between runners and controls for serum hepcidin levels midseason, suggesting that hepcidin was not chronically elevated with sustained high training loads.…”
Section: Discussionsupporting
confidence: 93%
“…The reason for selecting a group of male junior world elite rowers is based on their high absolute total hemoglobin mass (Treff et al, 2014) and the fact that they undergo a training regime that is associated with a heavy metabolic load, especially during training camps (Steinacker et al, 2000). We hypothesized, based on findings by Ishibashi et al (2017) in female runners, that serum hepcidin levels are elevated in periods consisting of high training loads, compared to lower load phases, possibly affecting the iron status of high performance athletes in an unfavorable manner.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated hepcidin level was observed in response to different forms of physical activity such as long-distance running [25], NordicWalking [26,27], basketball [28] or rowing [29]. Thus, hepcidine activity is considered as a most important factor of iron homeostasis during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The intra‐assay coefficients of variation (CVs) for these assays were 1.7% for serum iron, 2.9% for Mb, 2.0% for CK, and 1.5% for hs‐CRP. Serum hepcidin and plasma IL‐6 levels were analyzed by enzyme‐linked immunosorbent assays (ELISA) using commercially available kits (R&D Systems) (Goto et al, 2018; Ishibashi et al., 2017). The intra‐assay CVs for the hepcidin and IL‐6 assays were 1.7% and 2.5%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Iron deficiency is the most common nutrient disorder in the world and is estimated to affect ~50% of the global population (McClung et al., 2009). Iron deficiency or anemia are also frequently observed among endurance athletes (Ishibashi, Maeda, Sumi, & Goto, 2017; Ma, Patterson, Gieschen, & Bodary, 2013). Exercise‐induced iron deficiency is traditionally believed to be related to several factors, including sweating, hemolysis, hematuria, and gastrointestinal bleeding (Zoller & Vogel, 2004).…”
Section: Introductionmentioning
confidence: 99%